2006
DOI: 10.1080/14767050600637937
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of maternal and umbilical serum TNFα levels in preeclamptic pregnancies in the intrauterine normal and growth-restricted fetus

Abstract: Pregnant women with severe preeclampsia had significantly higher maternal and umbilical serum TNFalpha levels than those in the normotensive controls. Our findings and other reports indicate that TNFalpha may participate in the pathogenesis and sequelae of preeclampsia with and without IUGR. The results of excessive umbilical serum activity of tumor necrosis factor alpha (TNFalpha) in preeclamptic pregnancy complicated by intrauterine growth restriction (IUGR) may suggest additional changes and dysfunction of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 15 publications
2
28
0
Order By: Relevance
“…Inflammation is a part of the pathogenesis and is considered as one of the adverse pregnancy outcomes (51)(52)(53)(54). CRP, IL-6 and TNF-α are increased with preeclampsia, (55)(56)(57)(58), intrauterine growth restriction (IUGR) (51,52,59), and preterm labor/birth (60)(61)(62)(63) (55)(56)(57)(58). At the present study, subjective sleep quality is in significant correlation with abortion (P = 0.000).…”
Section: Discussionmentioning
confidence: 54%
“…Inflammation is a part of the pathogenesis and is considered as one of the adverse pregnancy outcomes (51)(52)(53)(54). CRP, IL-6 and TNF-α are increased with preeclampsia, (55)(56)(57)(58), intrauterine growth restriction (IUGR) (51,52,59), and preterm labor/birth (60)(61)(62)(63) (55)(56)(57)(58). At the present study, subjective sleep quality is in significant correlation with abortion (P = 0.000).…”
Section: Discussionmentioning
confidence: 54%
“…Increased levels of TNF α have been reported in the serum of pregnancies complicated with IUGR [35]. Amarilyo et al [36] showed higher levels of TNF α in the cord blood of IUGR infants and suggest that a state of inflammation exists in such infants.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of diseases, not associated with any external stimuli or injury, are known to induce high plasma levels of several cytokines including TNF-α. In healthy patients, the plasma level of TNF-α is generally smaller than 1 pg/mL, but its concentration can be abnormally high in the presence of atherosclerosis, [9][10][11][12] during tumorigenesis and tumor growth, 13 in patients with rheumatoid arthritis, 14 in women undergoing pre-eclamptic pregnancies, 15 and in obese individuals. 16 In incidences of acute trauma, elevated circulating levels of TNF-α have also been reported, including, but not limited to, traumatic brain injury 17 and hemorrhagic shock.…”
Section: Introductionmentioning
confidence: 99%